Hysteresis and Eddy Currents Effects Simulation in Idling Mode of the Transformer - Yarymbash D.S.; Kotsur M.I.; Yarymbash S.T.; Divchuk T.Ye. (Problems of the Regional Energetics, 2019)
The design parameters errors of the power transformer in idle mode can reach 15-20%. or more, because engineering techniques disregard the all factors. To reduce the error of engineering techniques modifying the circuit-analytical model. However, their field of application is limited. Therefore, the aim of the work is to develop interconnected circuit and field models that ensure high accuracy of idling parameters by allow for the parameters of the external network, transformer design features and nonlinear magnetic properties of electrical steel, asymmetry and non-sinusoidal idling currents. To achieve this aim, an improved approach is proposed. The scientific novelty of this approach provides conjugation of the external network objects, represented by the elements of the circuit model, with the testing transformer. For idle mode, it is represented as a spatial magnetic field model. The reduction of the computational time was performed by doubling cancellation of the volume of 3D three-phase transformer domain and the conformal transition to the 2D geometric domain. Determination of the effective magnetic characteristics of electrical steel according to single-phase idling experiment data, allows taking into account the combined effect of hysteresis and eddy currents, design and technological factors on the specific losses and magnetization power. This ensures high accuracy of the description of the interrelation between magnetic flux density and magnetic field strength, reducing of current error and relative errors in the calculation of idling losses up to 1.41% and 1.2% for the 3D model and up to 5.18% and 3.2% for the 2D model.